The Social Construction of State in South America. the Cross-Border Legacy of Jorge Gelman [la Construcción Social del Estado en Sudamérica: El Legado Transfronterizo de Jorge Gelman] - Pinto-Vallejos, J (Institute of Argentine and American History "Dr. Emilio Ravignani", 2022)
As a tribute to Jorge Gelman, this article summarizes the results of comparative research on early state formation in three South American countries: Argentina, Peru and Chile. Focusing on the hegemony-restoration efforts conducted by three “caudillo” regimes (those of Juan Manuel de Rosas, Ramón Castilla and Diego Portales), it explores cases of negotiation, inclusion and exclusion of popular actors in a dynamic it has named “social state-building”. It concludes that, starting from a common task of state-formation, the three experiences under inspection applied different strategies and doses of compulsion and seduction, resulting in equally different outcomes in terms of plebeian support and social inclusion. © 2022, Institute of Argentine and American History "Dr. Emilio Ravignani". All rights reserved.
Keywords: Caudillos; Plebeian actors; Post-Independence Latin America; Social state-building